Phytochemical Profile, Antioxidant Activity and Anticancer Activity of Gamma-Irradiated Black Rice Bran (Oryza sativa L.) Ethanolic Extract: In-Vitro and In-Silico Study - Rukmana, Rizal Maarif; Silfarohana, Rantika; Putra, Aditya Dwi Permana; Devi Safrina; Dian Susanti; Nur Rahmawati Wijaya; M Bakti Samsu Adi; Muhammad Evy Prastiyanto; Yanuar Ashari Cahyaningrum; Rina Nurmaulawati; Weka Sidha Bhagawan (Science and Technology Indonesia, 2025)
Black rice is a food crop with black pigments, which helps reduce the risk of various diseases and improve health. One way to improve food quality and avoid food contaminants is by irradiating. This study evaluated the phytochemical profile, antioxidant activity, and anticancer activity of irradiated black rice bran extract (IBRBE) in vitro and in silico. Black rice was irradiated with a Gamma cell 220 type irradiator at a 7.5 kGy/hour dose rate. Extraction of irradiated black rice bran was carried out using the maceration method. Phenolic and flavonoid components were quantified using the Folin–Ciocalteau and AlCl3 methods, respectively. Phytochemical compounds were identified by liquid chromatography-high-resolution mass spectrometry (LC HRMS). The antioxidant activity of IBRBE was carried out against 2,2-diphenyl-1picrylhydazyl (DPPH). The cytotoxic activity of IBRBE against WiDr cells (colorectal cancer) and Vero (nonhuman cell lines) used the MT test method. Prediction of the inhibitory mechanism of compounds in the extract against target proteins EGFR and GPX7 was carried out in silico. Total phenolics and flavonoids were 2.57 ± 0.28 mg GAE/g and 19.12 ± 0.18 μg QE/ml, respectively. Twenty-four types of active compounds were obtained in IBRBE. The results of antioxidant activity obtained an IC50 value of 1198.45 ± 92.86 μg/ml. IC50 in WiDr cells and Vero cells were obtained at 36.08 ± 11.71 μg/ml and 570.58 ± 130.25 μg/ml, respectively. In silico results, the compound 4 Dodecylbenzene sulfonic acid has the highest binding affinity to the EGFR protein, with a value of -5.9. Meanwhile, the Monoolein compound has the highest binding affinity to the GPX7 protein, with a value of -5.4.